2016
DOI: 10.21093/di.v16i2.356
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Lesson Study in English Language Learning: A Case Study

Abstract: Lesson Study as a growing interest in the education world has attracted educators, experts, and professionals in the area to make use of it in improving the lessons-it also happens in Indonesia. Originally applied in the teaching of mathematics in Japan, now it turns to be used in other fields, and English is one of them. This paper highlights the guideline on Lesson Study and pictures its application in a private senior high school in Malang, East Java, Indonesia. The adaptation of Lesson Study is interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Walker (2011) reported that her learning study practice demonstrated evidence for more "language-aware" science teachers and empowered these teachers by making them feel more competent in a contentbased education context in. Another study from the Indonesian context authored by Nashruddin and Nurrachman (2016) investigated the lesson study model in a case study design in teaching EFL at high school context. Drawing attention to the inclusive characteristic of the model, they suggested that inclusion of all ideas while co-developing lessons play an important role in the success of this model.…”
Section: International Researchmentioning
confidence: 99%
“…Walker (2011) reported that her learning study practice demonstrated evidence for more "language-aware" science teachers and empowered these teachers by making them feel more competent in a contentbased education context in. Another study from the Indonesian context authored by Nashruddin and Nurrachman (2016) investigated the lesson study model in a case study design in teaching EFL at high school context. Drawing attention to the inclusive characteristic of the model, they suggested that inclusion of all ideas while co-developing lessons play an important role in the success of this model.…”
Section: International Researchmentioning
confidence: 99%
“…In this manner, it can be said that using lesson study nationally and in other courses could contributes to both teachers' in-service professional development and students' learning. According to related literature, there are a lot of research about lesson study contributions to students' achievement especially in English and mathematics courses (Boran & Tarım, 2016;Coşkun, 2017;Kıncal & Beypınar, 2015;Koçak et al, 2018;Nashruddin & Nurrachman, 2016;Saito et al, 2015). The results of the study about teachers' views about lesson study are parallel to international and national studies' results (Boran & Tarım, 2016;Bozkuş et al, 2017;Cheung & Wong, 2014;Gonzalez & Deal, 2017;Günay, Yücel-Toy, & Bahadır, 2016;Howell & Saye, 2016).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The third is by Nashruddin and Nurrachman (2016) carried out a case study about the implementation of a lesson study in English language learning in Malang, East Java. They administered interviews and observations to investigate the effectiveness of lesson study in English language classrooms.…”
Section: A R T I C L E I N F Omentioning
confidence: 99%